RELATIONSHIP OF FOOD CONSUMPTION PATTERNS WITH INCREASING BLOOD PRESSURE IN ADULTS - Harianto, Susilo (Journal of Vocational Nursing, 2020)
Introduction: A healthy diet is a way or effort in regulating the number and type of food with certain intentions such as maintaining health, nutritional status, preventing or helping to cure disease. Blood pressure is the power caused by the heart that contracts like a pump, so that blood continues to flow in the blood vessels. A person's blood pressure can be more or less than the normal value limit. The trigger factor for changes in blood pressure is one of them about food consumption patterns, such as consuming excess salt. Methods: The purpose of this study was to determine the relationship of food consumption patterns with increased blood pressure. The design of this study uses analytics using the Case Control and sampling approach that is used is a non probability sampling with a number of 60 people and the number of samples taken by 36 respondents. Data collection used questionnaires coded, scored, tabulated and analyzed using the Chi-Square test. Results: The results of the study were 20 respondents (56%) with dietary patterns that did not fit the diet, 20 respondents (56%) with high blood pressure, from the Chi-Square analysis of 0,000 showed a significant value, meaning H0 was rejected or there was a relationship between consumption patterns food with increased blood pressure. Conclusion: Based on the results of the study, it can be concluded that there is a relationship between food consumption patterns and an increase in blood pressure.